Effects of dietary Chinese yam polysaccharide copper complex on growth performance, immunity, and antioxidant capacity of broilers - Zhang, Jinzhou; Jin, Yan; Cao, Mengmeng; Deng, Jiahua; Chang, Yadi; Shi, Mingyan; Miao, Zhiguo (Frontiers in Veterinary Science, 2023)
Chinese yam polysaccharide (CYP) has received attention in recent years owing to its positive nutritional and medicinal characteristics. Copper is an essential trace metal in animals, which plays an important role in iron absorption and hemoglobin synthesis. However, no published study has evaluated Chinese yam polysaccharide copper complex (CYP-Cu) as a dietary additive in broilers. This study was conducted to investigate the effects of dietary CYP-Cu on growth performance, immunity, and oxidative resistance in broilers. A total of 360 1-day-old 817 broiler chickens were randomly divided into 4 groups, with 3 replicates of 30 birds each and were fed a basal diet with the addition of 0 g/kg (control group), 0.02 g/kg, 0.10 g/kg, and 0.50 g/kg CYP-Cu. The feeding trial lasted 48 d. On d 28 and d 48, 6 broilers in each group were slaughtered, respectively. Then the parameters of growth and carcass, serum biochemistry, immunity, and antioxidation, and the expression level of hepatic antioxidative genes were investigated. The results showed that compared with the control group, the supplementation of dietary CYP-Cu could improve the indexes of the growth, carcass, serum biochemistry, immunity and oxidation resistance in broilers, such as ADG, SR, SEWR, EWR, PMP, LMR, ALB, HDL, IGF-1, T3, T4, GH, INS, IgM, IgA, IgG, IL-2, IL-4, IL-6, C3, C4, T-SOD, T-AOC, GSH-Px, GSH-ST; these parameters in the 0.10 g/kg CYP-Cu experimental group were significantly increased (P < 0.05) in the total trial period, with the exceptions that FCR and serum LDL, MDA were decreased in the total trial period. In addition, the antioxidative gene mRNA expression of CAT, Nrf2, SOD1, and SOD2 were upregulated in the liver (P < 0.05). These results indicated that the supplementation of dietary CYP-Cu improved the growth, immunity, and oxidation resistance of broilers, and the addition of 0.10 g/kg CYP-Cu in broiler diets is recommended, which suggests that CYP-Cu may be a promising green feed additive in the poultry industry.